Last child on the prairie: geo-progressions, mental maps, and community-based sense of place among Kansas third graders - Larsen, Thomas Barclay (Kansas State University, 2016)
A question exists on how cultural backgrounds influence the paths students take to understand cultural geography and construct mental maps of their communities. This thesis draws on the interconnections among student multiculturalism, geo-progressions (learning trajectories in geography), and perception of the environment at the community scale. As a result of the Road Map for 21st Century Geography Education, geo-progressions have received increased attention by geography education researchers. The majority of the effort to-date has focused on the first theme of the National Geography Standards: the world in spatial terms (Standards 1-3). This study attempts to deconstruct and rethink a geo-progression by considering multiple paths to learning Geography Standard Six, "how culture and experience influence people's perceptions of places and regions." The study incorporates the concept of community, a major theme for third grade as indicated in the Kansas Standards for History, Government, and Social Studies. During this longitudinal study, students were asked to make mental maps and talk about their community-based sense of place twice during part of the 2015-2016 school year. Third-grade classrooms from four demographically distinct areas of Kansas were surveyed: Manhattan, Garden City, Horton, and Junction City. The first session was conducted in September 2015. In January 2016, the same students were asked to perform the same tasks to assess any temporal differences. Mental maps and interviews were coded and analyzed to assess the spectrum of how students perceive a spatial sense of community over time. Interviews with teachers helped document classroom-to-classroom differences in how the concept of community was incorporated into the teaching effort.
Keywords: Geography; Mental maps; Sense of place; Geo-progressions; Learning progressions; Education